Mitigation of manganese with zeolites in waters of the Mantaro River, Jauja, Junín - Gómez Mandujano, Adrian Valentin (2022)
Technological progress develops industrial processes that impact the environment with the generation of waste. In the Mantaro river basin, the waters are contaminated by mining and surrounding populations. The National Water Authority (ANA) reports that at point RMant 12 an increase in manganese values is observed in its waters. at 200m Upstream is the intake of the agricultural irrigation channel left bank of the Mantaro Valley (RMBT), a reference point for the investigation. The objective of this study is to mitigate the manganese content with respect to the ECA 3 standards (0.20 mg/L). The investigation carried out in the laboratory demonstrated, in the case of synthetic water, a mitigation of 55% for the manganese content with the treatment of clinoptilolite-type zeolites. In the practice of the treatment carried out under the same conditions for the samples of water contaminated with manganese from the Mantaro River, the manganese content decreased by 32%. It is concluded that manganese mitigation has been carried out according to adsorption by zeolites, in multilayers according to Freundlich. Research on clinoptilolite is recommended to integrate it into decontamination methods for rivers in our country.